The role of religious coping in predicting the quality of life dimensions in women with breast cancer - Zahra Nikmanesh; Elham Khagebafgi; Behjat Kalantari (Golestan University of Medical Sciences, 2018)
Introduction: Quality of life is an important issue in chronic diseases, especially in cancer. Considering the religion in quality of life is important. Therefore, this study aimed to determine the role of religious coping in predicting the quality of life dimensions in patients with breast cancer. Methods: The study was a descriptive- correlation. The study population was the patients with breast cancer referred to the referral medical center of Kerman city in 2015. The sample included 121 patients who were selected by available sampling method. The variables were measured using the religious coping questionnaire and the quality of life questionnaire for breast cancer patients. Data were analyzed using Pearson correlation coefficient and Step-Wise Regression Test. Results: The results showed that there was a positive and significant relationship between functional dimension with religious activities, benevolent assessment, and active religious activities. The symptoms dimension had an inverse and significant relationship with religious activities. There was also a positive and significant relationship between the general health dimension with religious activities, benevolent assessments and active religious activities. The regression analysis indicated that benevolent assessment was a predictor for functional dimension (Beta=0.26). ReIigious activities were an inverse predictor for symptoms dimension (Beta= - 0. 1 8), and active religious activities were a predictor for general health quality of life (Beta=0.31). Conclusion: The dimensions of positive religious coping including religious activities, benevolent assessment, active religious activities can improve the quality of life of patients with breast cancer in functional, symptoms and general health dimension. Keywords: religion, quality of life, breast cancer